Retraction: Rajbhandari S, et al. Cardiac Resynchronization Therapy for Heart Failure. Journal of Advances in Internal Medicine 2012;01(02):65-8 - Editor, The (Journal of Advances in Internal Medicine, 2013)
It was brought to our attention that the article, "Cardiac Resynchronization Therapy for Heart Failure" JAIM | volume 01 issue 02 | July-December 2012 page 65, contains this passage in its introduction: “Heart failure is a clinical syndrome resulting from a structural and functional disorder of the heart that impairs the ability of the ventricles to fill with or eject blood to fulfil the demands of the body, or does so in expense of increased filling pressures.” Unfortunately, this passage is not attributed and was taken from an earlier publication: http://informahealthcare.com/doi/abs/10.3109/9780203089965.001. There are additional instances of plagiarism in the article. Given the weight of evidence offered in the report by Jeffrey Beall (Associate Professor, Scholarly Initiatives Librarian, Auraria Library, University of Colorado Denver, 1100 Lawrence Street, Denver, Colorado 80204 USA), the article has been retracted from the journal JAIM | volume 01 issue 02 | July-December 2012, page 65-8. DOI: http://dx.doi.org/10.3126/jaim.v2i2.8783 Journal of Advances in Internal Medicine 2013;02(02):81